Observational characteristics of cloud-radiation-precipitation during 2019 drought period in Yunnan of Southwest China - Yuwei Tan; Xinqiang Zhou; Bing Chen; Jiandong Li; Guo Lin; Xiaohong Liu; Tao Luo (Climate Dynamics, 2026)

Improved Madden–Julian oscillation simulation using the modified moist physical parameterizations for a global climate model - Xiaohan Li; Yanluan Lin; Xiao Zhou; Yiran Peng; Xiaomeng Huang (Climate Dynamics, 2026)

Evaluation of tropical cyclone genesis frequency in FGOALS-g3 large ensemble: mean state and interannual variability - Tingyu Zhang; Tianjun Zhou; Xin Huang; Wenxia Zhang; Xiaolong Chen; Pengfei Lin; Lijuan Li (Climate Dynamics, 2024)

Indirect effect of diabatic heating on Mei-yu frontogenesis - Yang Hu; Yi Deng; Yanluan Lin; Zhimin Zhou; Chunguang Cui; Chao Li; Xiquan Dong (Climate Dynamics, 2022)

Added value of kilometer-scale modeling over the third pole region: a CORDEX-CPTP pilot study - Xu Zhou; Kun Yang; Lin Ouyang; Yan Wang; Yaozhi Jiang; Xin Li; Deliang Chen; Andreas Prein (Climate Dynamics, 2021)

The contrasting effects of thermodynamic and dynamic processes on East Asian summer monsoon precipitation during the Last Glacial Maximum: a data-model comparison - Yong Sun; Haibin Wu; Masa Kageyama; Gilles Ramstein; Laurent Z. X. Li; Ning Tan; Yating Lin; Bo Liu; Weipeng Zheng; Wenchao Zhang; Liwei Zou; Tianjun Zhou (Climate Dynamics, 2021)
The Last Glacial Maximum (LGM; 21 ka BP) was the most recent glacial period when the global ice sheet volume was at a maximum. Therefore, the LGM can be used to investigate atmospheric dynamics under a climate that differed significantly from the present. This study quantitatively compares pollen records of boreal summer (June–July–August) precipitation with the PMIP3 LGM simulations. The data-model comparison shows an overall agreement on a drier than pre-industrial East Asian summer monsoon (EASM) climate. Nevertheless, 17 out of 55 records show a regional precipitation increase that is also simulated over the additional land mass area due to sea level drop. The thermodynamic and dynamic responses are analyzed to explain a drier LGM EASM as a combination of these two antagonistic mechanisms. Relatively low atmospheric moisture content was the main thermodynamic control on the lower LGM (relative to pre-industrial levels) EASM precipitation amounts in both the reconstructions and the models. In contrast, two dynamic processes in relation to stationary eddy activity act to increase EASM precipitation regionally in records and simulations, respectively. Precipitation increase in records is explained by dynamic enhancement of the horizontal moisture transport, while dynamic enhancement of the vertical moisture transport leads to simulated precipitation increase over the specific region where landmass was exposed during LGM along continental coastlines of China due to significant drop in sea level (relative to pre-industrial levels). Overall, the opposing effects of thermodynamic and dynamic processes on precipitation during the LGM provide a means to reconcile the spatial heterogeneity of recorded precipitation changes in sign, although data-model comparison suggests that the simulated dynamic wetting mechanism is too weak relative to the thermodynamic drying mechanism over data-model disagreement regions.

Improved decadal prediction of Northern-Hemisphere summer land temperature - Bo Wu; Tianjun Zhou; Chao Li; Wolfgang A. Müller; Jianshe Lin (Climate Dynamics, 2019)

Dynamical impact of parameterized turbulent orographic form drag on the simulation of winter precipitation over the western Tibetan Plateau - Xu Zhou; Kun Yang; Anton Beljaars; Huidong Li; Changgui Lin; Bo Huang; Yan Wang (Climate Dynamics, 2019)

Declining diurnal temperature range in the North China Plain related to environmental changes - Weitao Xue; Jianping Guo; Yong Zhang; Shunwu Zhou; Yuan Wang; Yucong Miao; Lin Liu; Hui Xu; Jian Li; Dandan Chen; Huan Liu (Climate Dynamics, 2019)

Interannual variability of Eastern China Summer Rainfall: the origins of the meridional triple and dipole modes - Chao He; Ailan Lin; Dejun Gu; Chunhui Li; Bin Zheng; Tianjun Zhou (Climate Dynamics, 2017)

How much of the interannual variability of East Asian summer rainfall is forced by SST? - Chao He; Bo Wu; Chunhui Li; Ailan Lin; Dejun Gu; Bin Zheng; Tianjun Zhou (Climate Dynamics, 2016)